Activation of uveolymphatic outflow pathway after non-penetrating glaucoma surgery without filtering bleb: case reports - V. Kumar; K.A. Abu Zaalan; M.A. Frolov; A.S. Shradqa; G.N. Dushina; A.I. Bezzabotnov; Z.Sh. Rustamova (РМЖ "Клиническая офтальмология")
V. Kumar1,2, K.A. Abu Zaalan1, M.A. Frolov1, A.S. Shradqa2, G.N. Dushina1,2, A.I. Bezzabotnov2, Z.Sh. Rustamova1 1RUDN University, Moscow, Russian Federation 2LLC Center of Eye Microsurgery “PRO zrenie”, Moscow, Russian Federation The authors propose a modified technique of non-penetrating filtering glaucoma surgery for primary open-angle glaucoma (POAG) to improve the uveoscleral outflow. The study enrolled 11 patients with POAG. A novel surgical technique included two steps. The first step was modified deep sclerectomy and cyclodyalysis with collagen implant placed into the supraciliary space. The second step (after 7–10 days) was YAG laser trabeculotomy. Surgical site and adjacent areas were examined by optical coherence tomography (OCT). After 6 months, mean IOP significantly reduced by 52% (from 30.0±10.3 mm Hg to 14.6±5.0 mm Hg, р=0.0004) while the number of IOP-lowering medications reduced by 79% (from 2.9±1.0 to 0.6±0.4, р=0.000001). The aqueous humor outflow occurred through conjunctival lymphatic vessels without filtering bleb formation, as illustrated by OCT. Postoperative complications were minor and easy-to-treat. Three case reports are discussed. Keywords: open-angle glaucoma, glaucoma surgery, conjunctival lymphatics, filtering bleb, non-penetrating glaucoma surgery, uveolymphatic outflow pathway. For citation: Kumar V., Abu Zaalan K.A., Frolov M.A. et al. Activation of uveolymphatic outflow pathway after non-penetrating glaucoma surgery without filtering bleb: case reports. Russian Journal of Clinical Ophthalmology. 2021;21(2):–115. DOI: 10.32364/2311-7729-2021-21-2-108-115.